Enhancing River Cleanliness and Waste Management: A Community Service Initiative with Plastic Fischer in Lengkong District Bandung - Suwandi Suwandi; Linahtadiya Andiani; Amaliyah Rohsari Indah Utami; Hertiana Bethaningtyas Dyah Kusumaningrum; Endang Rosdiana; Asep Suhendi; Casmika Saputra; Dudi Darmawan (Journal of Innovation and Community Engagement, 2025)
A community service, initiated by the Department of Physics Engineering at Telkom University, addresses the issue of plastic pollution in Lengkong subdistrict, Bandung. Through educational lectures, impactful sanitation activities, and advanced waste management technologies—including partnerships with international organizations—this initiative endeavors to resolve the pressing problem of plastic waste. Among the techniques employed are interactive cleanup days, educational lectures on recycling, and the application of cutting-edge technologies such as incinerators and imidazolium ionic liquids. The partnership with Plastic Fischer Germany, which actualizes SDG 17 (Partnerships for the Goals) and provides advanced technology and global expertise, was crucial for the program's success. The outcomes indicate a reduction in plastic waste, heightened environmental awareness, and the successful implementation of sustainable methods. This study concludes that achieving significant environmental change necessitates the integration of academic research with global cooperation and community engagement. The program's impact can be sustained and amplified through further expansion, ongoing education, and enhanced collaboration.